Towards an Autonomous Sailboat Navigation Control Architecture - Araújo, André; Guerra, Raphael; Mankina, Vishali; Preux, Philippe; Distante, Cosimo; Vasconcellos, Charles; Brandão, Diego; Gonçalves, Luiz; Clua, Esteban (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
Unmanned surface vessels of sailboat type are becoming important platforms for tasks such as surveillance and environmental monitoring. However, making them fully autonomous remains a challenge due to the complexity of their operating environments. In this paper, we propose a unified control architecture for autonomous sailboats that integrates low-level control strategies, such as PID for rudder control and fuzzy logic for sail adjustment. These traditional control techniques are adapted to the sailboat’s dynamics and have been experimentally validated in real-world scenarios. Future work will focus on developing a hierarchical reinforcement control (HRC) system, integrating Artificial Potential Fields (APF) and A* for high-level path planning and obstacle avoidance and Proximal Policy Optimization (PPO) for low-level control.